The social class as a dialectical category: towards a reconstruction - Rodríguez Rojo, Jesús (Nómadas. Critical Journal of Social and Juridical Science, 2017)
Due to the changes that have taken place in the last decades, the revision and re-reading of the theories is a must for researchers. This paper tries to offer an interpretation of the category of social class from an analysis in a logical-systematical way of Karl Marx´s Capital, 150 years after its first edition. In order to do that, we develop, from this oeuvre´s structure, a travel around its most important categories and its relationship with the social classes in the capitalist mode of production. Finally, we point out some essential ideas to think the social classes and the class struggle in the current social formations.
Keywords: Marxist theory; social class; class consciousness; class struggle.